1995
DOI: 10.1247/csf.20.275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Participation of Cytoskeleton of Heart Muscle Cells during the Invasion of Trypanosoma cruzi.

Abstract: ABSTRACT. The participation of heart muscle cells (HMC) cytoskeleton during its interaction withTrypanosoma cruzi was investigated. Pre-treatment of heart muscle cells with cytochalasin B (CB) or D (CD) prior to 1 and 3 h of interaction with T. cruzi inhibited the uptake of parasites by about 65%and 75%. T. cruzi was not able to invade fixed HMC, and fixed parasites were not internalized in either normal and CD-treated HMC. Transmission electron microscopy showed cell membraneprojections of HMCenclosing the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Studies carried out by several groups have shown that involvement of host cell actin with cytochalasins interferes with the internalization of trypomastigote forms into vertebrate cells (Barbosa et al, 1995;Burleigh et al, 1995;Burleigh et al, 1998;Caler et al, 2000;Carvalho et al, 1999;Mortara et al, 1999;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991). In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out by several groups have shown that involvement of host cell actin with cytochalasins interferes with the internalization of trypomastigote forms into vertebrate cells (Barbosa et al, 1995;Burleigh et al, 1995;Burleigh et al, 1998;Caler et al, 2000;Carvalho et al, 1999;Mortara et al, 1999;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991). In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982). In other situations, however, it has been shown that cytochalasin treatment even enhances parasite penetration (Caler et al, 2000;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991;Sibley et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed parasites were never seen inside cardiomyocytes, neither live parasites did invade fixed cells. Our data do not preclude the possibility of additional mechanism(s) of penetration that might require more active participation of the parasites for complete invasion to occur, but indicate that endocytosis is the main process involved in the uptake of metacyclic forms of T. cruzi by cardiomyocytes (Barbosa & Meirelles 1995). In a recent paper, De Souza et al (1998) suggested that both active penetration and typical phagocytosis can be used by the parasites to invade macrophages and Vero cells, and that both process can occur in the same cell.…”
mentioning
confidence: 60%
“…Cruzipain has an N-terminal catalytic domain linked to an antigenic C-terminal extension, the gp25 [61,62]. Structural characterization of the oligosaccharide chains revealed the presence of sulfated residues that are essential for cruzipain recognition by IgG antibodies from the serum of chagasic patients [63,64]. This peptidase is localized in different cell compartments, depending on the life cycle stage.…”
Section: Family C1 (Cruzipain and Others)mentioning
confidence: 99%